The Desired Integration between Language Planning and Educational Planning in Algeria - قرفة, زينة (LANGUAGE ART, 2019)
The planning process is dynamically linked to all types of work and life activities. A successful person performs the work on a systematic and purposeful planning basis by adopting the principle of rational and proper planning in his work and his life activities. Planning is, therefore, necessary in education like in economic and social affairs, especially as people's lives have become more complex developing rapidly in the shadow of globalization. Algeria has sought, through public policy, to adopt planning that encompasses various aspects of life, especially educational planning.